PERBEDAAN VOLUME PEMBERIAN AIR TERHADAP PERTUMBUHAN VEGETATIF PADI GOGO VARIETAS INPAGO UNSOED PARIMAS DI DISTRIK HUBIKIAK KABUPATEN JAYAWIJAYA: Differences of water supplying volume on vegetative growth of gogo rice inpago unsoed parimas variety in hubikiak district, jayawijaya regency - Anti Uni Mahanani; E Kogoya (Fakultas Pertanian Universitas Palangka Raya, 2022)
Upland rice is rice grown on dry land. The growth and production of upland rice plants are highly dependent on the availability of water. The water requirement for plants is determined by the volume or amount of water given to the plant. The purpose of this study was to determine the effect of water volume on the vegetative growth of upland rice varieties Inpago Unsoed Parimas. The research site is in the Hubikiak District, Jayawijaya Regency from June to October 2021. The method used is Completely Randomized Block Design (RAKL). Types of treatment are C1: water volume 250 ml polybag-1; C2: water volume 500ml polybag-1; C3: water volume 750 ml polybag-1; C4: water volume 1000 ml polybag-1. Parameters observed were: plant height, number of leaves, number of tillers, fresh and dry weight of plants, length of plant roots. The results of this study were the volume of water applied to the vegetative growth of upland rice varieties Inpago Unsoed Parimas on plant height and number of leaves aged 6 WAP and 8 WAP; the number of tillers aged 4 MST, 6 MST, 8 MST; plant fresh weight and root length. The water volume of 750 ml polybag-1 (C3) is the best water volume for the vegetative growth of upland rice of the Inpago Unsoed Parimas variety in the Hubikiak District, Jayawijaya Regency